'For all are born to the Ideal': Joseph Joachim and Bettina von Arnim. Issue 4 (12th February 2021) - Eshbach, Robert Whitehouse
Abstract: Although Joseph Joachim came of age in the milieu of the German Romantic salon, his biographers have largely ignored the critical influence of women on his artistic development. Amongst Joachim's many mentors, Bettina von Arnim's sway over the young musician is difficult to overstate. Once an intimate friend of Goethe and Beethoven, Bettina was an ardent music lover and amateur composer with outspoken aesthetic views. Through her mentorship, Joseph was confirmed in the Romantic cult of Beethoven veneration that Bettina helped create, as well as in Kunstreligion—the sacralization of art—as practiced in the Arnim household. Significantly, Bettina also helped influence Joachim away from Franz Liszt, whom she had at first revered, but with whom she quarreled. Using many hitherto unpublished sources, this article explores the influence that Bettina had on the young Joachim, and through him on conflicts and attitudes toward music current in the long nineteenth century.